Construction of Overseas Social Responsibility Image of Chinese State-Owned Enterprises Based on Corpus: Overseas Social Responsibility Image of Chinese State-Owned Enterprises - Zhou, Yajuan; Zhu, Wenzhong; Liu, Xiaoqin (Advances in Social Sciences Research Journal, 2024)
As the "cornerstone" of the socialist economy with Chinese characteristics and the "pioneer" in expanding international markets, state-owned enterprises’ overseas social responsibility image directly affects the nation’s image and reputation. Drawing on the latest achievements in discourse analysis, this study constructs a multidimensional analytical framework for the overseas social responsibility image of Chinese state-owned enterprises based on a corpus. Using state-owned enterprise social responsibility reports as the corpus, the study examines the linguistic features of the texts and the constructed social responsibility image from the perspectives of thematic words and phrases, intertextuality and interdiscursivity, modal verbs, and explores the underlying socio-cultural context. The findings of the research are as follows: 1) State-owned enterprise social responsibility reports construct multiple social responsibility images, including those of loyal party patriots, guardians of social stability and sustainability, practitioners of shared prosperity, industry leaders, and promoters of firm theoretical beliefs, thereby promoting traditional culture. 2) Furthermore, the reports exhibit positive traits such as openness, diversity, innovation, inclusivity, moderation, and friendliness. The research also indicates that the multifaceted and three-dimensional corporate social responsibility image of state-owned enterprises is closely related to their unique mission and status, as well as China’s distinctive cultural context. This study also aims to provide insights into the construction of social responsibility images for non-state-owned enterprises.